2017
DOI: 10.4081/mrm.2017.258
|View full text |Cite
|
Sign up to set email alerts
|

Nasal muco-ciliary transport time alteration: efficacy of 18B glycyrrhetinic acid

Abstract: Background: Mucociliary clearance is the main self-clearing system of the nasal cavity and paranasal sinuses. This is a very important means of non specific defence against continuous organic and inorganic contamination conveyed by air. It works by trapping particles and microorganisms in the mucus and then by transporting the mucous film to the pharynx where it is eliminated with a cough or swallowed. Its congenital or acquired abnormalities are involved in the occurrence of widespread infectious and often se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Interestingly, the direction of mucociliary transport was pointed posteroinferiorly in all turbinate mucosa in the present study. Observations in previous in vivo human studies using tracers, such as saccharin, radioisotope, dye, and charcoal powder, have indicated that mucociliary transport on the medial surface of the inferior turbinate is directed to the posterior [26][27][28][29]. We examined the lateral surface mucosa of the turbinate in the present study and obtained a similar result.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, the direction of mucociliary transport was pointed posteroinferiorly in all turbinate mucosa in the present study. Observations in previous in vivo human studies using tracers, such as saccharin, radioisotope, dye, and charcoal powder, have indicated that mucociliary transport on the medial surface of the inferior turbinate is directed to the posterior [26][27][28][29]. We examined the lateral surface mucosa of the turbinate in the present study and obtained a similar result.…”
Section: Discussionsupporting
confidence: 70%